Aud Cognitive Development in Dolupore State Kindergarten by Utilizing Plant Learning Media - Maria Fatima Palu; Veronik Tuga; Clotilda Mori; Maria Jenia Nena; Maria Natalia Defatima Tai; Maria Susanti Anu (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
Early childhood is a group of children who are in a unique growth and development process. Early childhood education is the most fundamental education because the child's development in the future is largely determined by various meaningful stimulations given from an early age. its various potentials. The method is carried out by teaching directly at the Dolupore State Kindergarten school. Through teaching activities it can help the growth and development of early childhood, by helping children to recognize letters and also various types of plants that are in the surrounding environment. simple problems in everyday life in a flexible and socially acceptable way and apply knowledge or experience in new contexts, think logically, cover various differences, classify, pattern, take initiative, plan, and know cause and effect, think symbolically, including the ability to recognize, name, and use the concept of numbers, recognize letters, and be able to present various objects and their imagination in the form of images (Permendikbud No 137 of 2014).